Answer:
28.26
Step-by-step explanation:
I hope this helps!
Answer:
welll there no like answers to give here so i dont know might want to check what you post before you post it
Step-by-step explanation:
To solve this function, all we need to do is substitute -4.3 in for wherever "x" appears and then simplify.
f(x) = 7.45x + 33.7; x = -4.3
f(-4.3) = 7.45(-4.3) + 33.7
f(-4.3) = -32.035 + 33.7
f(-4.3) = 1.665
This means that, when x = -4.3, f(x) = 1.665.
Note: It may help to remember that, in a function such as this, f(x) can be thought of as the "y" value that corresponds to the given "x" value (in fact, when writing it out with words, f(x) is the same as "function of x"). And, if you are given a value for f(x), then the opposite is true. Just substitute in the value given for f(x) and solve for x.
Hope this helps!
Wait for area, wouldn't you just times 13 and 5 and get 65 and then times 23?